Relevansi Maqashid Syariah dalam Kebijakan Perlindungan Perempuan dan Anak pada Hukum Keluarga di Indonesia - Nazifah Hanafiah (Integrated Education Journal, 2024)
This research explores the relevance of maqashid sharia the law policy for women and children in Indonesian law. As the main principle of Islamic law, maqashid sharia aims to protect five fundamental aspects of humans, namely religion (hifz ad-din), mental (hifz an-nafs), intelligence (hifz al-aql), offspring (hifz an-nasl), and property (hifz al-mal). In the context of family law, the implementation of maqashid sharia can strengthen the protection of women and children, especially on the issues of custody, domestic violence, and discrimination. This research uses a qualitative approach based on literature review to analyze and connected the positive laws, such as Marriage Law No. 1 of 1974 and the Compilation of Islamic Law (KHI), with Islamic values. The results show that the application of maqashid sharia allowing family law to reform being fair and responsive to what community needs, especially children and women’s groups that have high risk with what we mention above Maqashid sharia-based policies also have the potential to overcome social challenges such as patriarchal norms, and create a balance between legal and moral aspects. Thus, the application of these principles not only supports family justice and welfare, but also strengthens a legal system that is inclusive and relevant to the Indonesian context.